Language vitality of Malaysian Hakka dialect / Kim Fong Choo - Choo, Kim Fong (UiTM Cawangan Johor, 2024)
The rise of globalization and the interconnections of information have both facilitated the integration of human life but posed a threat to the survival of languages, particularly minority languages and dialects. In the multilingual context of Malaysia, minority languages and dialects encounter obstacles due to the prevalence of dominant languages. This research focuses specifically on the Hakka dialect spoken by Malaysian Chinese and aims to investigate its current status across different age groups. To achieve this objective, primary and secondary research materials were gathered through literature review, questionnaire surveys, interviews, and observations. Subsequently, the collected data was assessed and analysed using the nine criteria outlined in UNESCO 's Language Vitality and Endangerment document from 2003. These analyses serve to demonstrate the vitality of the Hakka dialect within Malaysia. Research has revealed that the Hakka dialect continues to exhibit a high degree of dynamism. However, with the gradual disappearance of the younger generation's involvement in its development, the endangerment of the dialect is becoming increasingly severe. Therefore, prompt implementation of human intervention measures is imperative.